Singularidades do trabalho gerencial em um hospital acreditado - Andreia Guerra de Oliveira (2012)
The survival of hospitals, either public or private, has been a great challenge. It is felt that health managers have attempted to search for quality improvements and process management, and the AH-hospital accreditation process for the provision of assistance to become more suited to continuous improvements. The accreditation is an important tool to organize the work efficiently and effectively, leading hospitals to go through several changes, among which the development of continuous improvement of the quality of patient care and improvements in organizational performance, providing confidence to community service. This study aimed to understand the work of the middle manager in a large hospital with Excellence Accredited by the methodology of the ONA. This is a qualitative case study conducted in a large private hospital in Belo Horizonte. Data were collected through interviews with semi-structured, with 12 managers of different professional categories. The sample was defined by the saturation criterion data. The ethical aspects were met with approval by the Research Ethics Committee of UFMG Hospital and signing the WIC. From the data analysis used the content analysis. With the data analysis produced the profile of managers and were built four thematic categories, which are: participation of the nurse manager in the process of hospital accreditation, the two sides of the hospital accreditation, quality instruments in the AH and the "new "challenges of management function, and people management: strategies of managers in achieving accreditation with excellence. The results showed that the insertion of the organization in the process of hospital accreditation changes occurred in the organization and consequently in the daily activities of the manager. The managers felt challenged and realized that the management became more complex, which lnes required more knowledge and skills. From the perspective of managers, accreditation has positive aspects that stand out, and negative aspects that impact on managerial work. There was a change of actions, formatting a management function before and after the implementation of hospital accreditation with Excellence. For the scope of accreditation was fundamental to Excellence training and development of people, the strategies used by managers to involve all staff in the process and also support from senior management at all stages of accreditation and in all sectors of the hospital . For managers to hospital accreditation was extremely relevant. However, there are many challenges. It is believed that the biggest challenge is to change the current health care model, focusing on the real needs of the patient and, in general, is believed to enter the hospital in the health system, not allowing them to operate as an island in the midst of other institutions . The commitment to accreditation should reach a greater number of institutions and thus increase the probability of delivering quality care to the entire population. It is believed that after this process will further contribute to an improved quality of care.